Եղիա Տեմիրճիպաշյան գրաքննադատը - Դեմիրճյան, Պետրոս (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Егия Темирчипашян (1851–1908) – западноармянский писатель, философ, педагог, редактор, один из самобытных деятелей новой армянской литературы второй половины XIX века – помимо теоретических вопросов, в ходе своей публицистической деятельности, естественно, занимался и проблемами литературной критики. В многочисленных публикациях теоретического характера Темирчипашян, подробно исследуя «Что такое поэзия», в частности «личная и безличная литература», анализировал необходимость литературной критики, критерии оценки современной литературы, проблемы истинного отражения современного этапа истории, на основе всего этого выражая свое отношение и оценку творчества классических и современных писателей. В 1890-е годы литературная жизнь Армении характеризовались напряженными дискуссиями, в которых Е. Темирчипашян играл немаловажную роль. Он не только не избегал споров, но и признавал их полезность, будучи убежден, что в литературной жизни «всегда царит однообразие без дискуссий». Yeghia Temirchipashyan (1851–1908) is a Western Armenian writer, philosopher, teacher, and editor. He is one of the original figures of the new Armenian literature of the second half of the XIX century; in addition to theoretical issues, in the course of his journalistic activity, naturally, he also dealt with the problems of the literary criticism. In his numerous publications of theoretical nature, Temirchipashyan thoroughly studied the issue “What is poetry”, in particular, “personal and impersonal literature”, analyzed the need for literary criticism, criteria for evaluating the contemporary literature, problems of true reflection of the modern stage of history. On the basis of all this, he expressed his attitude and appreciation of the works of the classical and modern writers. In the 1890s, the literary life of Armenia was characterized by intense discussions, in which E. Temirchipashyan played an important role. Not only did he not avoid disputes, but also recognized the usefulness of debates, being convinced that in literary life “there is always monotony without discussion”.
Keywords: Հայ գրականագիտություն; Հայ գրողներ